Pengaruh Modal terhadap Profitabilitas Peternakan Ayam Pejantan - Ahmad Muhayan Arif; Jeni Susyanti; Ety Saraswati (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract The aim of this study to find out the effect of owner’s equity and foreign equity on the income of micro, small and medium enterprises at Desa Candirengo, Kecamatan Singosari, Malang. The population of this study were rooster breeders in Desa Singosari totally 31 breeders and with a sample totally 15 breeders. The research was quantitative research using secondary data to collect the data, namely the financial report of the breeders. The financial report used are six times on harvests and in one harvest for two months. The data analysis method in this study used the normality test and the classical assumption test. The results of this study indicate that intern equality and extern equality have a positive influence on the income of micro, small and medium enterprises at Desa Candirengo, Kecamatan Singosari, Malang. Keyword: Owner’s Equality, Foreign Equality, profitabilty.